A comparison of European eel Anguilla anguilla eDNA concentrations to fyke net catches in five Irish lakes. Issue 4 (25th May 2020) - Weldon, Laura; O'Leary, Ciara; Steer, Mark; Newton, Lyn; Macdonald, Heather; Sargeant, Stephanie L.
Abstract: The European eel, Anguilla anguilla, is classified as critically endangered by the IUCN. To protect what remains of the European eel population, accurate monitoring methods for this species are important. Environmental DNA (eDNA) techniques are gaining popularity for ecological monitoring of aquatic organisms because they are sensitive and noninvasive. This study directly compared catch data from a standardized fyke‐net fishing survey with a single species A. anguilla eDNA survey in five freshwater lakes in Ireland. The eDNA was recovered by the filtration of water samples and amplified by quantitative real‐time polymerase chain reaction (qPCR). European eel eDNA was reliably determined in 83% (70/84) of surface water samples collected from lakes classified as having high, medium, and low eel populations. In addition, there was a positive association between the eDNA concentrations recovered and the eel population classification with lower eDNA concentrations in lakes classified as low eel population lakes. Similar amounts of A. anguilla eDNA were detected in water samples collected from open water and shore‐side, suggesting shore sampling is an adequate method for eel detection. Together, the results demonstrate that eDNA sampling is more sensitive for detecting eel presence in low eel population environments than standard survey methods and may be a useful noninvasive tool for monitoring A. anguilla species distribution. Abstract : This study directly compared catch data from a fyke‐net fishing survey with an Anguilla anguilla eDNA survey in five freshwater lakes in Ireland. Eel eDNA was reliably determined in 83% (70/84) of surface water samples collected. The results demonstrate that eDNA sampling is more sensitive for detecting eel presence in low eel population environments than standard survey methods.